Synthesis of some α, β-unsaturated ketones from 3-acetyl-4-methylcoumarin. - Thanh, Nguyễn Ngọc; Thành, Bùi Tất; Thảo, Nguyễn Minh (Vietnam Journal of Chemistry, 2012)
3-Acetyl-4-methylcoumarine was prepared by cyclization reaction of 2-hydroxy-acetophenone with ethyl acetoacetate. The product was then transformed by condensation with aromatic aldehydes to form a series of new α,β-unsaturated ketones (12 compounds) and (2,3-dihydrobenzofur-2-yl) (4-methylcoumarin-3-yl)ketone. Their structure have been confirmed by IR, 1H-NMR and MS spectroscopic data.  Biological activities of these compounds have been tested for bactericidal and fungicidal; it is found that the derivatives α,β-unsaturated ketones exhibit high activity.